Edukasi Pencegahan Penyakit Cacingan, Diare, dan Infeksi Salmonella melalui Gaya Hidup Sehat di SDN Balet Baru 02 Sukowono Jember - Adjie Bangun Linuweh; Agustianingsih Agustianingsih; Ekta Zalfa Zahirah; Gabriel Fabiano Lumbantobing; Rofiyatul Hasanah; Salwa Raihani Nadine Syahdani; Siti Ayu Puspitasari; Oria Alit Farisi; Muhammad Ghufron Rosyady; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Helminthiasis, salmonella infection, and diarrhea represent significant health challenges stemming from inadequate understanding of clean and healthy behavioral practices, particularly among elementary school children who lack sufficient awareness regarding personal hygiene and environmental sanitation. The community service program aimed to enhance elementary school students' comprehension of diseases that readily compromise children's immune systems. Teaching methods employed included classroom material delivery using visual media, handwashing simulations, and educational games. The activity was conducted at SDN Balet Baru 02, Sukowono Sub-district, northern Jember Regency, which borders Bondowoso Regency, involving 24 sixth-grade students as the primary target group. The selection of sixth-graders was based on the consideration that such age represents an optimal period for character formation and cognitive development in children. Program evaluation demonstrated a substantial increase in student knowledge, evidenced by the comparison between pre-test results showing 40% achievement and post-test results reaching 80%. The interactive approach proved effective in conveying health materials to elementary school-aged children. The community service program contributed to the advancement of child-centered health education methods that are more interactive and easily comprehensible, with the expectation that SDN Balet Baru 02 students would be able to implement the acquired knowledge to become future generations more attentive to personal hygiene and health.